The role of differentiation in the relationship between the leader and the follower in enhancing the outcomes of the strategic decision: Analytical study of the opinions of a sample of Top management teams (Department managers) in the Ministry agency for Administrative and Financial Affairs in the Iraqi Ministry of Interior - ثامر حمـزة طالب الطائي; الهام ناظــم الشيباني (Iraqi Journal for Administrative Sciences, 2024)
This study aimed to test the effect of differentiation in the relationship between the leader and the follower, which is a one-dimensional variable on the outcomes of the strategic decision with its indicators (decision quality, decision understanding, commitment to the decision) through an intentional sample of Top management teams (Department managers) in the directorates of the Ministry agency for administrative and financial affairs in the Iraqi Ministry of Interior, using a set of statistical analyzes, including mean, standard deviation, correlation coefficient (Pearson) and simple regression through statistical programs (SPSS V. 25) and (Amos v.20). The data was collected from the field reality by relying on the main data collection tool (the questionnaire), as 226 questionnaires were distributed to 47 directorates and were examined through the analysis The confirmatory factor, and using the aggregation method, the data of the respondents were collected into groups, so that we have (47) team or working groups. Through the results of the statistical analysis of the responses of the research sample, it was found that the differentiation in the relationship between the leader and the follower (LMXD), which is based on personal and social relationships, negatively affects the outcomes of the strategic decision, and on the contrary, if the type of differentiation in the relationship between the leader and follower is based on performance, it may affect Positively on the outcomes of the strategic decision. and based on the conclusions that were reached, it was Presenting a set of recommendations, the importance of which is that leaders should enhance working relationships with members of top management teams who are characterized by high performance and avoid personal and social relationships at work. On the contrary, leaders should reduce relationships with members who are characterized by low performance and tend to form personal and social relationships, which negatively affects positively on the outcomes of strategic decisions.